2014
DOI: 10.1002/cplu.201300430
|View full text |Cite
|
Sign up to set email alerts
|

Essential‐Oil Analysis of Irradiated Spices by Using Comprehensive Two‐Dimensional Gas Chromatography

Abstract: Four different spices were packaged either under 100 % nitrogen or using ambient air, and then gamma‐irradiated at different doses. The essential oils of the original spices and of those irradiated were obtained by hydrodistillation. Changes to the essential‐oil compositions due to irradiation and effects of packaging were detected and compared by using comprehensive two‐dimensional gas chromatography (GC×GC). The use of GC×GC provided better separation and more reliable results. It enabled ready detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…It was also reported that the application of MAP prior to irradiation of seasoned beef meatballs reduced lipid oxidation, degradations in color, and sensory properties during storage (Gunes, Ozturk, Yilmaz, & Ozcelik, ; Gunes, Yilmaz, & Ozturk, ). We found in our previous work that irradiation under a modified atmosphere (100% N 2 ) decreased some of the quality degradation in spices such as loss of essential oil content, alteration of the essential oil composition, and loss of color (Kirkin, Mitrevski, Gunes, & Marriott, , ).…”
Section: Introductionmentioning
confidence: 95%
“…It was also reported that the application of MAP prior to irradiation of seasoned beef meatballs reduced lipid oxidation, degradations in color, and sensory properties during storage (Gunes, Ozturk, Yilmaz, & Ozcelik, ; Gunes, Yilmaz, & Ozturk, ). We found in our previous work that irradiation under a modified atmosphere (100% N 2 ) decreased some of the quality degradation in spices such as loss of essential oil content, alteration of the essential oil composition, and loss of color (Kirkin, Mitrevski, Gunes, & Marriott, , ).…”
Section: Introductionmentioning
confidence: 95%
“…Aerobic Mesophilic total count [8], spore forming bacteria count [9], total yeast/mold count [10], coliforms count [11], Staphylococcus aureus [12,13] and Escherichia coli presence/absence [14] were evaluated in triplicate. Next, the appropriate plates containing 30-300 bacterial colonies and 15-150 fungal colonies, respectively were selected and counted [15]. The sample microbial contamination was calculated and reported in terms of cfu/g.…”
Section: B Microbial Analysismentioning
confidence: 99%